Audit Energi Listrik dan Analisis Peluang Penghematan pada Industri Es Kristal Bodas - Nur Achya Afifudin; Ida Widihastuti (MEDIA ELEKTRIKA, 2025)
This study aims to analyze electrical energy consumption and identify energy-saving opportunities in Bodas Crystal Ice Industry through an energy audit. The method applied is a quantitative descriptive energy audit involving historical consumption data, load measurements, and Specific Energy Consumption (SEC) analysis. The average electricity consumption was 6,253 kWh per month, of which ice production and refrigeration accounted for more than 95%. The initial SEC was 386 kWh/ton. After correcting the combined scenario to avoid double-counting freezer savings, the estimated consumption decreased to 4,852 kWh per month, equivalent to a 22.4% saving, while SEC decreased to 299.5 kWh/ton. These values represent technical-economic estimates that require verification after implementation. Keywords: Energy Audit, Specific Energy Consumption, Ice Production Industry, Refrigeration System, Energy Saving